Translating Arabic Aphorismsi into Indonesian Language: Its Strategies and Equivalence | Tarjamah Al-Hikam Al-'Arabīyah ilā Al-Lughah Al-Indūnīsīyāh: Istirātījīyātuhā wa At-Takāfu' Fīhā - Zainal Muttaqin; N. Lalah Alawiyah; Awalia Rahmi Zahara; Fatima El Zahraa (Universitas Islam Negeri Palangka Raya, 2022)
This research aims to reveal the strategies used in translating Arabic aphorisms into Indonesian language and to measure the equivalence at word level in the book entitled Seratus Mahfudzot written by As